2021
DOI: 10.1002/lt.26054
|View full text |Cite
|
Sign up to set email alerts
|

Black Race Is Associated With Higher Rates of Early‐Onset End‐Stage Renal Disease and Increased Mortality Following Liver Transplantation

Abstract: Black race is a risk factor for end-stage renal disease (ESRD). Racial disparities in the risks of early and long-term renal complications after liver transplantation (LT) have not been systematically studied. This study evaluated racial differences in the natural history of acute and chronic renal insufficiency after LT. This was a retrospective single-center cohort study of 763 non-Hispanic White and 181 Black LT recipients between 2008 and 2017. Black race was investigated as an independent predictor of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Fourth, variables were captured at LT, and post‐LT changes (e.g., interval post‐LT changes to insurance status 20 ) or behaviors 21 (e.g., health adherence, alcohol/tobacco use) were not evaluated. While we did adjust for a number of co‐morbidities at LT, other comorbidities are unknown in UNOS and may differ by race, particularly hypertension which is more common in Blacks and is associated with higher rates of renal insufficiency 22 . Differences in hypertension prevalence may contribute to survival differences for Blacks; however, a recent national study shows stable trends among young to mid‐aged US adults for the prevalence, awareness, treatment, and control of hypertension across racial groups 23 suggesting hypertension cannot account entirely for the increasing post‐LT survival disparity for Blacks over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, variables were captured at LT, and post‐LT changes (e.g., interval post‐LT changes to insurance status 20 ) or behaviors 21 (e.g., health adherence, alcohol/tobacco use) were not evaluated. While we did adjust for a number of co‐morbidities at LT, other comorbidities are unknown in UNOS and may differ by race, particularly hypertension which is more common in Blacks and is associated with higher rates of renal insufficiency 22 . Differences in hypertension prevalence may contribute to survival differences for Blacks; however, a recent national study shows stable trends among young to mid‐aged US adults for the prevalence, awareness, treatment, and control of hypertension across racial groups 23 suggesting hypertension cannot account entirely for the increasing post‐LT survival disparity for Blacks over time.…”
Section: Discussionmentioning
confidence: 99%
“…While we did adjust for a number of co-morbidities at LT, other comorbidities are unknown in UNOS and may differ by race, particularly hypertension which is more common in Blacks and is associated with higher rates of renal insufficiency. 22 Differences in hypertension prevalence may contribute to survival differences for Blacks; however, a recent national study shows stable trends among young to mid-aged US adults for the prevalence, awareness, treatment, and control of hypertension across racial groups 23 suggesting hypertension cannot account entirely for the increasing post-LT survival disparity for Blacks over time. Finally, examining specific policy changes over the study period, including expansion of health insurance coverage by the Affordable Care Act, addition of sodium to the MELD allocation…”
Section: Unos-based Studies Mediated Only the Minority Of The Black V...mentioning
confidence: 99%
“…In comparing Black patients meeting SLKT criteria by race‐adjusted and race‐unadjusted eGFR formulas, there was no difference in waitlist mortality between the groups, suggesting that differences in key patient outcomes may manifest in the posttransplant setting. ( 2 ) Indeed, we found that a higher proportion of patients reclassified as meeting SLKT criteria via the CKD pathway without race adjustment required short‐term kidney transplantation. These are important points as the safety‐net policies that govern access to kidney transplantation after LTA also rely on eGFR.…”
Section: Discussionmentioning
confidence: 82%
“…( 12‐14 ) Finally, Black patients have in increased incidence of ESRD and need for dialysis after LTA, which was recently shown with national registry data. ( 2 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation